Mortality and survival of semi-domesticated reindeer (Rangifer tarandus tarandus L.) calves in northern Finland - Nieminen, Mauri; Norberg, Harri; Maijala, Veikko (Rangifer, 2011)
During the period 1999 to 2004 the reindeer calf survival and mortality were studied in two reindeer-herding cooperatives and in five herding-groups in northern Finland, where in total 1725 calves were fitted with mortality indicating radio-transmitters fixed on expandable neck collars. The calves were weighed and marked at the age of 2-5 days in calving corrals and also during earmarking in June/July, when the age of calves was 2-8 weeks. The rate, timing and causes of mortality of calves were investigated. In 1999-2001 in Ivalo reindeer-herding cooperative 4.6% of radiocollared calves and in 2002-04 in Käsivarsi reindeer cooperative 5.2% was found dead. The average mortality of the calves radio-collared during calving time in May, and monitored to the end of October, was 6.7% in Ivalo and 9.0% in Käsivarsi. From July on, the average mortality rates varied between 1.8-5.7% among reindeer herding-groups. On average 54 and 42% of all radio-collared calves found dead in Ivalo and Käsivarsi cooperatives were attributed to predation, and golden eagle was the most significant cause of death in both cooperatives killing 0-3.5% of radio-collared calves in different study areas and years. Golden eagle predation accounted for 33-43% of all radio-collared calves found dead, 55-59% of the cases with identified cause of death and 80% of all identified predation. Most of the calves killed by golden eagle were found during July and August mainly in the open areas, as in highlands, bogs and clear-cut forest areas. The mean body weight of the calves radio-collared in May (weights adjusted on June 1st) and found dead during the summer was significantly (P<0.01) lighter than the mean weight of survivors both in Ivalo and Käsivarsi. Furthermore, the midsummer body weights of the calves (weights adjusted on July 1st) killed by all predators and by golden eagles were significantly (P<0.001) lower than the mean weight of surviving calves in both cooperatives. However, the weights did not differ between depredated calves and those calves that succumbed due to other causes than predation. The results of this study emphasize the relative importance of golden eagle as a mortality factor for reindeer calves in the northern part of the Finnish reindeer husbandry area.